Non-contact refractive index measurement based on fiber optic beam-through technique - Rahman, Husna Abdul; Harun, Sulaiman Wadi; Yasin, Moh; Ahmad, Harith (INOE, 2011)
A simple refractive index sensor for various concentrations of sodium chloride (NaCl) in de-ionized water is proposed and demonstrated. The beam-through technique is used to obtain output voltage of liquids with known refractive indices, namely methanol, de-ionized water, acetone and ethanol. Based on the output voltage of these liquids, the sensor characteristic curve is determined and the refractive indices of 2 % to 12 % sodium chloride concentrations are obtained. A sensitivity and detection limit of 23.07 mV/refractive index unit (RIU) and 2.28 × 10-3 RIU have been derived from measurements, respectively, with a linearity of more than 97 %. The fiber optic sensor is a promising alternative to other well-established methods for the measurement of liquid refractive index due to its simplicity of design, linearity, non-contact sensing, ruggedness and low fabrication cost.